Captivated by Liquidity – Theoretical Traps and Practical Mazes - Novák, Zsuzsanna; Tatay, Tibor (Public Finance Quarterly, 2021)
There is no uniform theoretical standpoint on the effects of changing interest rates and the role of money among economists. Though these disputes exercise a great influence on the economic policy measures adopted as well. For the management of the 2008 global financial crisis many central banks entered into forceful interest rate cuts to contribute to the revitalisation of the economy. The economic recession caused by the pandemic of 2020 again raises the issue how central banks can stimulate growth. In this study we deal with the liquidity trap issue attributed to Keynes. Keynes pointed out that there might exist a lower interest rate limit under which money demand becomes infinite. His conceptions put the foundations to the question, at what interest rate levels might the liquidity trap – a term coined later by Robertson – phenomenon become effective. He was followed by numerous renowned economists dealing with the conception. In this paper we are discussing the most important theoretical approaches – among others the views of Hansen, Hicks, Tobin, Patinkin, Krugman, Brunner and Meltzer and Eggertson. We provide an overview on the effects of low interest rate levels adopted by Japan, by the central banks of Japan, the USA and the ECB aimed at stimulating the economy. Based on the study it can be confirmed that central banks can contribute to economic growth keeping interest rates low and therewith fostering investment. Nevertheless, beyond keeping short-term interest rates low, it might be adequate to control interest rates of other maturities and, especially under deflationary expectations, central banks should express their prolonged commitment to low interest rates.